Thrombin generation assays are versatile tools in blood coagulation analysis: A review of technical features, and applications from research to laboratory routine. (26th September 2021) - Depasse, François; Binder, Nikolaus B.; Mueller, Julia; Wissel, Thomas; Schwers, Stephan; Germer, Matthias; Hermes, Björn; Turecek, Peter L.
Abstract: Thrombin is the pivotal enzyme in the biochemistry of secondary hemostasis crucial to maintaining homeostasis of hemostasis. In contrast to routine coagulation tests (PT or aPTT) or procoagulant or anticoagulant factor assays (e.g. fibrinogen, factor VIII, antithrombin or protein C), the thrombin generation assay (TGA), also named thrombin generation test (TGT) is a so‐called "global assay" that provides a picture of the hemostasis balance though a continuous and simultaneous measurement of thrombin formation and inhibition. First described in the early 1950s, as a manual assay, efforts have been made in order to standardize and automate the assay to offer researchers, clinical laboratories and the pharmaceutical industry a versatile tool covering a wide range of clinical and non‐clinical applications. This review describes technical options offered to properly run TGA, including a review of preanalytical and analytical items, performance, interpretation, and applications in physiology research and pharmacy.